A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (2018)

Acoustic communication in marine shallow waters: testing the acoustic adaptive hypothesis in sand gobies - Amorim, Maria Clara P.; Vasconcelos, Raquel O.; Bolgan, Marta; Pedroso, Silvia S.; Fonseca, Paulo J. (Journal of Experimental Biology, 2018)
Skip to Next Section Acoustic communication is an important part of social behaviour of fish species that live or breed in shallow noisy waters. Previous studies have shown that some fish species exploit a quiet window in the background noise for communication. However, it remains to be examined whether hearing abilities and sound production of fish are adapted to marine habitats presenting high hydrodynamism. Here, we investigated whether the communication system of the painted (Pomatoschistus pictus) and the marbled (Pomatoschistus marmoratus) gobies is adapted to enhance sound transmission and reception in Atlantic shallow water environments. We recorded and measured the sound pressure levels of social vocalisations of both species, as well as snapshots of ambient noise of habitats characterised by different hydrodynamics. Hearing thresholds (in terms of both sound pressure and particle acceleration) and responses to conspecific signals were determined using the auditory evoked potential recording technique. We found that the peak frequency range (100–300 Hz) of acoustic signals matched the best hearing sensitivity in both species and appeared well adapted for short-range communication in Atlantic habitats. Sandy/rocky exposed beaches presented a quiet window, observable even during the breaking of moderate waves, coincident with the main sound frequencies and best hearing sensitivities of both species. Our data demonstrate that the hearing abilities of these gobies are well suited to detect conspecific sounds within typical interacting distances (a few body lengths) in Atlantic shallow waters. These findings lend support to the acoustic adaptive hypothesis, under the sensory drive framework, proposing that signals and perception systems coevolve to be effective within local environment constraints.
8 citations (Crossref) [2022-09-21] Publisher: The Company of Biologists Ltd Section: Research Article

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)
9 citations (Crossref) [2022-09-21]

DISRUPT - Environmental Endocrine disruptors: Current situation in Macao, neurobehavioral effects and bioremediation strategies - Gonçalves, David (University of Saint Joseph, 2018)

FIGHT – Hormonal, pheromonal and genomic regulation of aggression in a fish model - Gonçalves, David (University of Saint Joseph, 2018)

Listening to the Environment: Importance of Early Acoustic Experience on Hearing and Development in Zebrafish - Vasconcelos, Raquel (University of Saint Joseph, 2018)

Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Research Projects: Petrology and Geochemistry of Igneous Rocks from Macao: Implications for the Crustal Evolution of Southern China - Dias, Ágata (University of Saint Joseph, 2018)

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish - Cardoso, Sara D.; Gonçalves, David; Goesmann, Alexander; Canário, Adelino V. M.; Oliveira, Rui F. (Molecular Ecology, 2018)
Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e., larger and older nest-holder males and smaller and younger sneaker males occur). Sneakers mimic both female's courtship behaviour and nuptial coloration to get access to nests and sneak fertilizations, and later in life transition into nest-holder males. Thus, this species offers the unique opportunity to study how the regulation of gene expression can contribute to intersex phenotypes and to the sequential expression of male and female behavioural phenotypes by the same individual. We found that at the whole brain level, expression of the sneaker tactic was paralleled by broader and divergent gene expression when compared to either females or nest-holder males, which were more similar between themselves. When looking at sex-biased transcripts, sneaker males are intersex rather than being either nest-holder or female-like, and their transcriptome is simultaneously demasculinized for nest-holder-biased transcripts and feminized for female-biased transcripts. These results indicate that evolutionary changes in reproductive plasticity can be achieved through regulation of gene expression, and in particular by varying the magnitude of expression of sex-biased genes, throughout the lifetime of the same individual.
6 citations (Crossref) [2022-09-21] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mec.14408
Keywords: RNA-seq; Salaria pavo; alternative reproductive tactics; behavioural plasticity; neurogenomic state; sex-biased gene expression

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a sub-tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2018)